2016
DOI: 10.1097/md.0000000000005136
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation for Budd–Chiari syndrome

Abstract: Background:The aim of the study was to report the detailed surgical techniques of living donor liver transplantation (LDLT) in patients with Budd–Chiari syndrome (BCS).Methods:Demographic and surgical techniques characteristics of 39 patients with BCS who underwent LDLT were retrospectively reviewed. Thirty-two of them had native vena cava inferior (VCI) preservation and 6 had retrohepatic VCI resection with venous continuity established by cryopreserved VCI (n = 4) or aortic graft (n = 2). In 1 patient, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Novel alternative techniques, aimed at eliminating stenosis or obstruction in the recipient IVC, are thus needed for LDLT in the context of BCS[ 6 ]. Some of them include cross-clamping the supra- and infrahepatic IVC and excising its thickened wall to create a wide orifice for graft implantation[ 7 ] or the V-Y plasty technique[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel alternative techniques, aimed at eliminating stenosis or obstruction in the recipient IVC, are thus needed for LDLT in the context of BCS[ 6 ]. Some of them include cross-clamping the supra- and infrahepatic IVC and excising its thickened wall to create a wide orifice for graft implantation[ 7 ] or the V-Y plasty technique[ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Yan et al [ 14 ] reported the first LDLT for BCS with IVC reconstruction using an interposed cryopreserved cadaveric IVC graft[ 14 ]. Since then, many other studies have addressed IVC reconstruction with interposing autologous veins[ 15 ], cadaveric venous allografts[ 3 , 7 , 16 - 18 ], cadaveric aortic allografts[ 7 , 17 - 20 ], synthetic material[ 12 , 13 , 18 ] or a combination of synthetic material and autologous vein[ 21 , 22 ] or venous allografts[ 18 , 23 ]. Table 2 provides a review of all cases found in the literature of LDLT for BCS with IVC resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Korean standardization of right-lobe LDLT suggests preservation of retro-hepatic IVC and unification venoplasty techniques for reconstruction of the inferior right hepatic vein [ 42 ], which was likewise performed in our center. Venous augmentation is frequently performed in highly experienced LDLT centers [ 41 , 43 , 44 ], and PTFE grafts [ 41 , 43 ] or homologous vascular grafts [ 43 , 45 ] can be used. Although remaining a rare complication after LDLT, IVC stenosis can be successfully treated by PTA [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…152,153 Although the evidence comes from a small series of cases, living donor liver transplant is a viable choice with acceptable survival rates (>70% at 5 years). 154,155 Treatment of recent NCPVT The aim of therapy for recent NCPVT is to prevent the extension of the thrombus to mesenteric veins and intestinal infarction. In addition, therapy for recent NCPVT must try to achieve portal vein recanalization to prevent the development of portal hypertension.…”
Section: Key Pointmentioning
confidence: 99%